2003
DOI: 10.1523/jneurosci.23-08-03439.2003
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Acuity is Enhanced in Blindness

Abstract: Functional imaging studies in blind subjects have shown tactile activation of cortical areas that normally subserve vision, but whether blind people have enhanced tactile acuity has long been controversial. We compared the passive tactile acuity of blind and sighted subjects on a fully automated grating orientation task and used multivariate Bayesian data analysis to determine predictors of acuity. Acuity was significantly superior in blind subjects, independently of the degree of childhood vision, light perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
252
5
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(290 citation statements)
references
References 38 publications
30
252
5
3
Order By: Relevance
“…On the one hand, the sample size for this test was low and the relationship was strong enough (beta = +39) that it might reach significance with a more fully powered study. On the other hand, several studies of tactile acuity in blind Braille readers have reported a similar result, finding no relationship between practice variables (e.g., being an early blind subject or being an avid present day Braille reader) and better tactile acuity (Goldreich & Kanics, 2003Van Boven et al, 2000).…”
Section: Discussionmentioning
confidence: 86%
“…On the one hand, the sample size for this test was low and the relationship was strong enough (beta = +39) that it might reach significance with a more fully powered study. On the other hand, several studies of tactile acuity in blind Braille readers have reported a similar result, finding no relationship between practice variables (e.g., being an early blind subject or being an avid present day Braille reader) and better tactile acuity (Goldreich & Kanics, 2003Van Boven et al, 2000).…”
Section: Discussionmentioning
confidence: 86%
“…d, Scatterplot of threshold versus distal phalanx surface area, with female (red) and male (blue) regression lines. Women: red Ⅺ; men: blue E. Kanics, 2003). We next investigated the cause of this tactile sex difference.…”
Section: Resultsmentioning
confidence: 99%
“…In the Duquesne experiments, we used a two-down one-up staircase, with 14 reversals per testing block, as described by Goldreich and Kanics (2003). The Duquesne data consisted of two testing blocks per participant, taken from a larger experiment of eight blocks (the two blocks were collected in a lit room with the participant's eyes open, corresponding to the McMaster testing condition; the other blocks, not relevant to the current study, tested different lighting conditions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies reported that blind subjects outperformed sighted subjects under certain conditions (Rossetti et al, 1996;Van Boven et al, 2000;Goldreich and Kanics, 2003;Gaunet and Rossetti, 2006;Alary et al, 2008). Thus, there is no consensus on the sensorimotor performance of blind subjects compared with normally sighted subjects.…”
Section: Performance Of Blind Versus Blindfolded Normally Sighted Submentioning
confidence: 92%